Nailing Down an Identity – The Voices of Six Carpentry Educators - Lisa Maurice-Takerei; Joce Jesson (New Zealand Journal of Teachers' Work)
This paper reports on a small research study in which six carpentry tutors at an urban polytechnic were interviewed regarding their identity and perceptions of their work as trades educators. Some preliminary findings suggest that the ‘occupational identity’ (Seddon, 2008) of trades educators as ‘teachers’ is less problematic than suggested (see Haycock & Kelly, 2009). This paper argues that notions of good teaching within Institutes of Technology and Polytechnics (ITPs) may be driven by normative/singular notions of pedagogy that do not recognize specific or ‘signature pedagogies’ (Shulman, 2005) active within trades education. It is suggested that further work in the area of ‘signature pedagogies’ for the trades will legitimise trade educator practice. However, it may challenge professional developers, teacher trainers and educational administrators within institutions to reconsider their assumptions about what constitutes ‘good teaching’ in a trade related environment.